Is a wake-up call in order? Review of the evidence for awake craniotomy. (January 2016) - Paldor, Iddo; Drummond, Katharine J.; Awad, Mohammed; Sufaro, Yuval Z.; Kaye, Andrew H.
Highlights: Awake craniotomy (AC) has been reported chiefly for resection of low grade gliomas. AC enables function preservation when resecting tumors in eloquent areas. Successful mapping and localization of function improves preservation of function. Preservation of complex function is best in experienced referral centers. AC is not consistent in its effect on extent of resection. Abstract: Awake craniotomy (AC) has been used in increasing frequency in the past few decades. It has mainly been used for resection of intrinsic tumors, but also, rarely, for other pathologies. The vast majority of reports specific to one pathology, however, have focused on resection of low grade glioma in the awake setting. Tumors in eloquent areas have mainly been resected when the patient is awake for the purpose of preservation of function. Motor function is the most documented, and most successfully preserved function. Other functions are harder to localize with direct electrical stimulation (DES), and thus more difficult to preserve. The success rate of DES localization correlates to the rate of function preservation. The effect of AC on extent of resection is inconsistent in the literature. Other functions, such as sensory and visuospatial recognition, have been protected during AC, but this is best performed in large, referral centers that have experience with the procedure. Other benefits to AC, such as cost-effectiveness and reduction in patient pain and anxiety, have also been reported.